Corrosion inhibition of carbon steel using fatty amide derivatives and an oxygen scavenger under elevated temperatures - Mariah Ibrahim, Izni; Suhailah Mohd Kassim, Ezan; Jai, Junaidah; Daud, Muhamad; Amin Hashim, Md (International Journal of Engineering and Technology, 2018)
In this study, fatty amides and sodium sulphite were introduced as corrosion inhibitor and oxygen scavenger respectively. The synergistic effect of corrosion inhibition of carbon steel in 3.5% sodium chloride solution was investigated under elevated temperatures (30, 40, and 50 Â°C). The corrosion inhibitor was synthesized using reflux reaction from material of palm fatty acid distillate. The performance of sodium sulphite as oxygen scavenger was tested using dissolved oxygen meter. The corrosion inhibition efficiency of the corrosion inhibitors was studied using the electrochemical test namely linear polarization resistance method. The results revealed that the combination of fatty amides and sodium sulphite inhibits the corrosion of carbon steel by reducing the concentration of dissolved oxygen in the solution and increased the inhibition efficiency.Â Â